Modified N-acyl-L-homoserine lactone compounds abrogate Las-dependent quorum-sensing response in human pathogen Pseudomonas aeruginosa - Ballante, Flavio; Turkina, Maria V.; Ntzouni, Maria; Magnusson, Karl-Eric; Vikström, Elena (Frontiers in Molecular Biosciences, 2023)
Quorum sensing (QS) is a mode of cell–cell communication that bacteria use to sense population density and orchestrate collective behaviors. The common opportunistic human pathogen Pseudomonas aeruginosa employs QS to regulate a large set of genes involved in virulence and host–pathogen interactions. The Las circuit positioned on the top of the QS hierarchy in P. aeruginosa makes use of N-acyl-L-homoserine lactones (AHLs) as signal molecules, like N-3-oxo-dodecanoyl-L-homoserine lactone (3O-C12-HSL). Disabling QS circuits by certain small-molecule compounds, known as quorum-sensing inhibitors (QSIs), has been proposed as a strategy to attenuate bacterial pathogenicity. In this study, four new AHL analogs were designed by incorporating a tert-butoxycarbonyl Boc group in amide and β-keto (3-oxo) moiety. Compounds were evaluated on a molecular and phenotypic basis as a QSI using the screening strategy linked to the assignment of the Las QS system in P. aeruginosa. Using a LasR-based bioreporter, we found that the compounds decreased LasR-controlled light activity and competed efficiently with natural 3O-C12-HSL. The compounds reduced the production of the cognate 3O-C12-HSL and certain virulence traits, like total protease activity, elastase activity, pyocyanin production, and extracellular DNA release. Furthermore, a quantitative proteomic approach was used to study the effect of the compounds on QS-regulated extracellular proteins. Among the four compounds tested, one of them showed the most significant difference in the appearance of the 3O-C12-HSL-responsive reference proteins related to QS communication and virulence, i.e., a distinct activity as a QSI. Moreover, by combining experimental data with computational chemistry, we addressed the effect of LasR protein flexibility on docking precision and assessed the advantage of using a multi-conformational docking procedure for binding mode prediction of LasR modulators. Thus, the four new AHL compounds were tested for their interaction with the AHL-binding site in LasR to identify the key interferences with the activity of LasR. Our study provides further insight into molecular features that are required for small-molecule modulation of LasR-dependent QS communication in P. aeruginosa. This should facilitate rational design of the next generation of antivirulence tools to study and manipulate QS-controlled fitness in bacteria and, thereby, handle bacterial infections in a new way.